Parents' experiences of using remote monitoring technology to manage type 1 diabetes in very young children during a clinical trial: Qualitative study. Issue 7 (24th March 2022) - Hart, Ruth I.; Kimbell, Barbara; Rankin, David; Allen, Janet M.; Boughton, Charlotte K.; Campbell, Fiona; de Beaufort, Carine; Fröhlich‐Reiterer, Elke; Ware, Julia; Hofer, Sabine E.; Kapellen, Thomas M.; Rami‐Merhar, Birgit; et al.
Abstract: Aims: To explore parents' experiences of using remote monitoring technology when caring for a very young child with type 1 diabetes during a clinical trial. Methods: Interviews were conducted with parents of 30 children (aged 1–7 years) participating in a trial (the KidsAP02 study) comparing hybrid closed‐loop insulin delivery with sensor‐augmented pump therapy. In both arms, parents had access to remote monitoring technology. Data analysis focused on identification of descriptive themes. Results: Remote monitoring technology gave parents improved access to data which helped them pre‐empt and manage glucose excursions. Parents observed how, when children were in their own care, they could be more absent while present, as their attention could shift to non‐diabetes‐related activities. Conversely, when children were others' care, remote monitoring enabled parents to be present while absent, by facilitating oversight and collaboration with caregivers. Parents described how remote monitoring made them feel more confident allowing others to care for their children. Parents' confidence increased when using a hybrid closed‐loop system, as less work was required to keep glucose in range. Benefits to children were also highlighted, including being able to play and sleep uninterrupted and attend parties and sleepovers without their parents. While most parents welcomed the increased sense of control remote monitoring offered, some noted downsides, such as lack of respite from caregiving responsibilities. Conclusions: Remote monitoring can offer manifold benefits to both parents and very young children with type 1 diabetes. Some parents, however, may profit from opportunities to take 'time out'.